A Comparative Study of Existing Data Mining Techniques for Phishing Detection - Shukla, M; Sharma, S (International Journal of Computer Sciences and Engineering, 2025)
Nowadays phishing become a major threat on internet. Phishing is a kind of attack for defacement of website in which attacker can access sensitive information of users. Phishers are one who create website same as the trusted website with the same content and designs of the trusted website. Phishing can be done through email, websites and malicious software to get intellectual information, business secrets or military secrets etc. This paper is explored the various researches for avoiding phishing and detecting phishing symptoms. Many researchers have been proposed various methods for algorithms for avoiding all conditions with the detection of phishing using data mining techniques so that any user can use internet effectively. This paper is based on Associative Classification methods of data mining for avoidance of phishing attack.